Estudio del Clima Organizacional en Teletrabajadores Suplementarios del Área Administrativa de una Empresa del Sector Aeroportuario (2024)
The present investigation aims to analyze the organizational climate of the supplementary teleworkers of the administrative area of a company in the airport sector in Bogota. It was carried out under a methodological framework with exploratory scope, mixed type of research, sequential transformational design, pragmatic approach, and with the participation of a sample of 20 supplementary teleworkers. For data collection, the Organizational Climate Scale (EDCO) and the focal group technique are applied, allowing a greater analysis and deepening of the information